Numerical Simulation of Mechanically Harvested Blueberry Based on EDEM - BAO Yudong; YANG Jie; ZHAO Yanling; LIU Xianli; LIANG Zhao; GUO Yanling (Journal of Harbin University of Science and Technology)
In order to study the causes of mechanical harvesting of blueberry fruits, to determine the distribution of fruit damage and to improve the penetration rate of domestic mechanical harvesting blueberries, based on the analysis of the working principle of harvesting machines, the discrete element method was used to study the mechanical harvesting process. The large number of fruit contact collision characteristics, based on EDEM simulation of blueberry mechanical harvesting process, the energy change after fruit contact collision in the harvesting process, the fruit damage degree was analyzed by energy change value, and the probability of fruit no damage was 79.33%. The probability of damage is 7.77%. The simulation results show that there is no mechanical damage in the process of mechanical harvesting. The mechanical harvesting can ensure the quality of blueberry fruit. This study can provide theoretical support for the promotion of domestic mechanical harvesting of blueberries.